2005
DOI: 10.1210/en.2005-0279
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens Up-Regulate the Fas/FasL Apoptotic Pathway in Lactotropes

Abstract: The Fas/FasL system provides the major apoptotic mechanism for many cell types, participating in cell turnover in hormone-dependent tissues. In the present study, we localized both Fas and FasL in anterior pituitary cells, mainly in lactotropes and somatotropes. The percentage of anterior pituitary cells showing immunoreactivity for Fas or FasL was higher in cells from rats killed in proestrus than in diestrus. Also, the proportion of pituitary cells from ovariectomized (OVX) rats expressing Fas or FasL increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…Interestingly, Candolfi et al had reported that Fas activation induces apoptosis of anterior pituitary cells from female rats, suggesting that FasL is involved in the maintenance of tissue homeostasis in the anterior pituitary gland and could have potential benefits for the treatment of pituitary adenomas (18)(19)(20)(21). In the present study, we detected the expressions of Fas and DcR3 on 3 pituitary adenoma cell lines.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…Interestingly, Candolfi et al had reported that Fas activation induces apoptosis of anterior pituitary cells from female rats, suggesting that FasL is involved in the maintenance of tissue homeostasis in the anterior pituitary gland and could have potential benefits for the treatment of pituitary adenomas (18)(19)(20)(21). In the present study, we detected the expressions of Fas and DcR3 on 3 pituitary adenoma cell lines.…”
Section: Introductionsupporting
confidence: 50%
“…Jaita et al detected that Fas and FasL are expressed in several anterior pituitary cell types from female rats, mainly in lactotropes and somatotropes. In addition, they reported that Fas activation induces apoptosis of lactotropes and somatotropes as well (21). It was also demonstrated that the somatolactotrophic tumor GH3 cell line and the corticotrophic tumor AtT20 cell line express Fas (31,32).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, our present data show that overexpression of TNF-in primary anterior pituitary cell cultures induced apoptosis of prolactin-and growth hormonebearing cells. We previously detected the expression of FasL and Fas in several anterior pituitary cell types from female rats, mainly in lactotropes and somatotropes (Jaita et al 2005b). In addition, we reported that Fas activation induces apoptosis of lactotropes (Jaita et al 2005b) and somatotropes as well (Jaita et al 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed that both TNF-and FasL induce apoptosis of anterior pituitary cells (Candolfi et al 2002, Jaita et al 2005b). Now, we overexpressed TNF-and FasL in primary cultures of anterior pituitary cells by infecting them with first-generation adenoviral vectors encoding TNF-(RAd-hCMV-TNF-), FasL (RAd-hCMV-FasL) or, as a control, -Gal (RAd-hCMV--Gal), under the control of the human cytomegalovirus promoter (hCMV).…”
Section: Tnf-and Fasl Transgene Expression In Normal Anterior Pituitamentioning
confidence: 99%
See 1 more Smart Citation